Enhancing selective encryption for H.264/AVC using advanced encryption standard - Abomhara, Mohamed; Zakaria, Omar; Khalifa, Othman Omran; Zaidan, Aos Alaa; Zaidan, Bilal Bahaa (International Association of Computer Science and Information Technology Press (IACSIT), 2010)
Multimedia information availability has increased dramatically with the advent of mobile devices. But with this availability comes problems of maintaining the security of information that is displayed in public. Many approaches have been used or proposed for providing security for information dissemination over networks, protection system classified with more specific as encryption information, and combination between video compression and encryption to increase information security. The strength of the combination between Video compression and encryption science is due to the nonexistence of standard algorithms to be used in video compression and encrypting secret video stream. Also there are many ways could be used in video encryption methods such as combining several different encryption methods with video compression to pass a secret video streaming. Furthermore, there is no formal method to be followed to discover an encrypted video. For this reason, the task of this paper becomes difficult. In this paper proposed a new system of video encryption is presented. The proposed system aim to gain a deep understanding of video data security on multimedia technologies, to investigate how encryption and decryption could be implemented for real time video applications, and to enhance the selective encryption for H.264/AVC. The system includes two main functions; first is the encoding/encryption of video stream, through the execution of two processes (the input sequences of video is first compressed by the H.264/AVC encoder, and the encoded bit stream (I-frame) is partially encrypted using AES block cipher). And the second function is the decryption/decoding of the encrypted video through two process (specify the encrypted I-frame stream, decryption of the I-frame, and decoding with H.264/AVC decoder). The system is implemented by using Matlab.